Data from: Kin grouping is insufficient to explain the inclusive fitness gains of conspecific brood parasitism in the common eider ... - Hervey, Samuel; Barnas, Andrew; Stechmann, Tanner; Rockwell, Robert; Ellis-Felege, Susan; Darby, Brian (Dryad, 2019)
Conspecific brood parasitism allows females to exploit other females’ nests and enhance their reproductive output. Here, we test a recent theoretical model of how host females gain inclusive fitness from brood parasitism. High levels of relatedness between host and parasitizer can be maintained either by; 1) kin recognizing and parasitizing each other as a form of cooperative breeding or 2) natal philopatry and nest site fidelity facilitating the formation of kin groups increasing the probability of parasitism between relatives nesting in close proximity. To address these two hypotheses we genotyped feathers and hatch membranes of common eiders (Somateria mollissima) from western Hudson Bay, using a non-invasive sampling methodology. We found that most instances of brood parasitism do result in inclusive fitness gains. However, a greater inclusive fitness was gained toward the host when she was parasitized by individuals with no nest of their own compared to those that parasitize and nest. Further, females ... : Hervey2019AlleleNamesFastA-formated file of allele names (as in "Hervey2019EiderGenotypes.csv") and their sequences. Allele names include the locus, length, and variant. For example, allele "Sfi01_120_A" is from locus "Sfi01", has length 120 nt, and is variant "A" of all alleles length 120 for that locus.Hervey2019EiderGenotypesComma-delimited file with genotypes for each of the eider nest bowl samples collected in 2016 and 2017.Hervey2019NestDataComma-delimited file with data for each nest.Hervey2019READMEContains descriptions for files, "Hervey2019AlleleNames.txt", "Hervey2019EiderGenotypes.csv", and "Hervey2019NestData.csv" ...